2021
DOI: 10.3390/ijerph18126343
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Scientific Facts vs. Conspiracy Theories: Is Science Failing to Pass Its Message?

Abstract: Science may be failing to convince a significant number of people about COVID-19 scientific facts and needed public health measures. Individual and social factors are behind believing conspiracy theories. Adults (N = 1001) were asked to rate their beliefs in various conspiracy theories circulating in social media, rate their psychological distress relating to COVID-19, rate their trust in science to solve COVID-19 problems, and rate their willingness to adhere to measures regarding social distancing and quaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
4
45
2
Order By: Relevance
“…Despite the possible involvement of further variables in the link between attitude and behaviour, it is a striking finding that COVID-19 conspiracy beliefs hadof all variables -the strongest direct association with adherence as well. Our results therefore add to a growing body of recent evidence for the significant impact of unwarranted beliefs and mistrust in science in the fight against the pandemic (Allington et al, 2020;Bierwiaczonek et al, 2020;Bruder & Kunert, 2021;Constantinou et al, 2021;Earnshaw et al, 2020;Freeman et al, 2020;Gratz et al, 2021;Imhoff & Lamberty, 2020;Pavela Banai et al, 2020Plohl & Musil, 2021;Pummerer et al, 2021;Reinders Folmer et al, 2020;Romer & Jamieson, 2020;Šrol et al, 2021;Teovanović et al, 2021Teovanović et al, , 2021. Remarkably, this result emerged in a sample that did not consist of particularly strong conspiracy believers.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Despite the possible involvement of further variables in the link between attitude and behaviour, it is a striking finding that COVID-19 conspiracy beliefs hadof all variables -the strongest direct association with adherence as well. Our results therefore add to a growing body of recent evidence for the significant impact of unwarranted beliefs and mistrust in science in the fight against the pandemic (Allington et al, 2020;Bierwiaczonek et al, 2020;Bruder & Kunert, 2021;Constantinou et al, 2021;Earnshaw et al, 2020;Freeman et al, 2020;Gratz et al, 2021;Imhoff & Lamberty, 2020;Pavela Banai et al, 2020Plohl & Musil, 2021;Pummerer et al, 2021;Reinders Folmer et al, 2020;Romer & Jamieson, 2020;Šrol et al, 2021;Teovanović et al, 2021Teovanović et al, , 2021. Remarkably, this result emerged in a sample that did not consist of particularly strong conspiracy believers.…”
Section: Discussionsupporting
confidence: 71%
“…Relatedly, previous studies found a positive relationship between COVID-19 conspiracy beliefs and the use of social media as source of information (Allington et al, 2020). An important step forward might thus for example be to encourage people to rely more on trusted sources (Constantinou et al, 2021;Pavela Banai et al, 2020).…”
Section: Limitations and Outlookmentioning
confidence: 95%
See 2 more Smart Citations
“…It has further been suggested that mistrust triggers biased information processing (e.g., lower analytical thinking and scientific literacy) which eventually results in conspiracy beliefs (Pierre, 2020). Recently, lack of trust in media (Bruder & Kunert, 2021;Lockyer et al, 2021;Su et al, 2021), government and public health institutions (Bruder & Kunert, 2021;De Coninck et al, 2021;Kim & Kim, 2021;Pummerer et al, 2021), and science (Constantinou et al, 2020;Eberl et al, 2021;Erceg et al, 2020) have also been shown to play a key role in fostering conspiracy beliefs about the origins of COVID-19. A large-scale cross-country comparison showed that in countries where people find fewer reasons to trust institutions (e.g., countries that lack rule of law), there are significantly higher levels of COVID-19-related and general conspiracy beliefs (Alper, 2021).…”
Section: Conspiracy Beliefs and Generosity Across 52 Countries During The Covid-19 Pandemicmentioning
confidence: 99%